Interferometric Locating the Waist of a Laser Beam - Vyacheslav A. Maslov; Konstantin I. Muntean (East European Journal of Physics, 2024)
An interferometric method for determining the location of a laser beam waist has been developed, which implements the dependence of the wavefront curvature on its distance to the waist. The initial laser beam, the waist location of which must be determined, is split by a shear interferometer into reference and information beams, which form a spatially non-localized interference field in reflected light. The period of the interference fringes observed in any cross-section of the interference field carries information about the location of the waist of the initial laser beam relative to this section. The distance from the waist to the plane of recording the period of the interference fringes is calculated using the formulas of Gaussian optics. The fundamental difference of this method from currently known ones allows for increasing the accuracy of the obtained result while simultaneously reducing the laboriousness of the measurement process.